KESULITAN BELAJAR MEMBACA DALAM PENERAPAN K13 PESERTA DIDIK KELAS I SEKOLAH DASAR - Nopitasari; Amir Hakim (Vokal: Jurnal Ilmiah Bahasa dan Sastra Indonesia, 2022)
The purpose of this study was to analyze the problems of students' learning difficulties in reading skills. This research uses a qualitative descriptive research type. This research was conducted at SDN 07 Parak Juar Batusangkar. The students in class I consist of 30 people, so the sampling used is purposive sampling. The data collection instrument in this study was the researcher himself (human instrument). With data collection techniques in the form of observation, interviews, and documentation. Data analysis techniques that have been collected in this study, consist of data collection, data reduction, data presentation, and conclusions. The results of the study were obtained that learning difficulties faced by students, namely students did not know and were able to memorize all the letters of the alphabet so that reading difficulties were caused by internal and external factors. Internal factors are physical factors, interests, and motivation. While external factors are from the teacher due to ineffective classroom management and curriculum that used by school can’t applied well, then factors from family is the lack of support for children at home. In this study, it can be concluded that the factors that cause learning difficulties for elementary school 1st class learners are not yet recognizing alphabetical letters and have not been able to distinguish letters so that when reading learners are still confused and make mistakes.